The role of hard phase carbides in tribocorrosion processes for a Co-based biomedical alloy. (September 2017) - Wang, Zhongwei; Yan, Yu; Xing, Lu; Su, Yanjing; Qiao, Lijie
Abstract: In order to enhance the wear resistance of the Co-based biomedical alloy, hard phase carbides were introduced into the alloy matrix. However, torn-off carbides can lead to abrasive wear and may increase the wear factor. In this study, the behaviour of carbides in the tribocorrosion processes of CoCrMo alloys was investigated. Scanning Kelvin probe force microscope (SKPFM) was used to evaluate the relative nobility of the carbides and their surrounding areas. The experimental results indicated that carbides can inhibit and block the movement of the stacking fault under plastic deformation. Carbides would be torn from the matrix during the tribocorrosion process, due to the preferential dissolution of the boundary area under the action of galvanic corrosion and tribological contact. Highlights: The referential dissolution of the carbide boundary area accelerates tribocorrosion. The stacking faults accumulate at the carbide boundaries resulting in micro-cracks. The carbide cluster can decrease the Volta potential of the surrounding matrix.